Rancang Bangun Sistem Informasi Persediaan Barang Berbasis Web Menggunakan Metode FIFO di PT Garuda Surya Raya - Kevin Aqila Artama; Novita Mariana (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
PT Garuda Surya Raya is a company engaged in the supplier of smartphone boxes. Inventory recording is still done manually, there is often a discrepancy between the number of goods in stock and the physical goods in the field. So that there is an error in the amount that results in delays in ordering goods and delays in the production process. Based on the above problems, the research objective is to design a web-based inventory information system at PT Garuda Surya Raya. The method used in this research is the FIFO method and the waterfall development system. Starting with looking for problems, suggestions, and needs from the warehouse admin. Then it is implemented and the system is tested to find out its weaknesses. This system was built using PHP and MySQL as the database. The results of the research are the system can simplify the process of recording incoming goods, and outgoing goods, recording stock opname, and making reports.